PENGARUH FASILITAS E-FILING DAN E-SPT TERHADAP KEPUASAN WAJIB PAJAK ORANG PRIBADI DALAM MELAPORKAN SPT (Studi Kasus Pada KPP Pratama Kota Batam) - Desrini Ningsih; Fany Rahma Sari; Heryenzus Heryenzus (JURNAL AKUNTANSI BARELANG, 2019)
The Directorate General of Taxes has provided facilities to taxpayers to report taxes with SPT using e-Filing facilities and e-SPT. E-Filing is an application made by the directorate general of taxes so that taxpayers do not have to bother to queue at the tax service office. While e-SPT is also an application of services made by the directorate general of taxes for taxpayers to be able to report their taxes more easily and not consume a lot of paper. The study was conducted aimed to determine the effect of e-Filing and e-SPT facilities on the satisfaction of individual taxpayers in reporting SPT. The sample used was 400 using the purposive sampling method. The results of this study indicate that e-Filing and e-SPT facilities have a positive and significant influence on taxpayer satisfaction. Evident from the value of t count is greater than t table. The value of t table is 1.966 while the value of t count is obtained for the variable e-Filing facility (X1) 8.624 with a significance of 0,000 and the facility variable e-SPT (X2) 10,899 with a significance of 0,000. Result F shows F count 384,649 with a significant probability of 0,000.